Visualization of sneeze ejecta: steps of fluid fragmentation leading to respiratory droplets - Scharfman, B. E.; Techet, A. H.; Bush, J. W. M.; Bourouiba, L. (Experiments in fluids, 2016)
Coughs and sneezes feature turbulent, multiphase flows that may contain pathogen-bearing droplets of mucosalivary fluid. As such, they can contribute to the spread of numerous infectious diseases, including influenza and SARS. The range of contamination of the droplets is largely determined by their size. However, major uncertainties on the drop size distributions persist. Here, we report direct observation of the physical mechanisms of droplet formation at the exit of the mouth during sneezing. Specifically, we use high-speed imaging to directly examine the fluid fragmentation at the exit of the mouths of healthy subjects. We reveal for the first time that the breakup of the fluid into droplets continues to occur outside of the respiratory tract during violent exhalations. We show that such breakup involves a complex cascade of events from sheets, to bag bursts, to ligaments, which finally break into droplets. Finally, we reveal that the viscoelasticity of the mucosalivary fluid plays an important role in delaying fragmentation by causing the merger of the droplet precursors that form along stretched filaments; thereby affecting the final drop size distribution farther downstream.